Efficiency Improvement and Analysis of Changes in Microstructure Associated to a Uniform Pressure Actuator - Arroyo, A.; Daehn, G. S.; Eguia, I.; Fernandez, J. I.; Garuz, I.; Jimbert P.; Silveira, E. (Institut für Umformtechnik - Technische Universität Dortmund, 2006)
During the 1st international Conference on HIGH SPEED FORMING held in Dortmund in 2004 a new forming coil giving significant advantages was presented in the framework of ongoing R&D programs at OSU (The Ohio State University). It established the improvement provided by the return path for currents induced in the workpiece. To quantify the mentioned improvement, Labein has performed classical cone forming experiments with both configurations and analyzed energetic efficiency using well known alloys, more precisely AA 6016 and 1050. Both deformation mechanisms and contour analysis of the specimens were studied. General purpose multi-turn coils provide pressure distributions not extended to the whole forming area, resulting in zones undergoing significant delay as die the deformation sequence is referred. As a result, varied deformation patterns can be found along the contour of a cone specimen formed in such way. Firstly, a macroscopic survey of the specimens shows that uniform pressure distributes deformation over the entire formed area during the deformation process. Secondly, the effect on efficiency provided by this new coil concept is focuses not only on the ability for distributing deformation, but on the energy required to create such deformation. Finally, to validate the whole simulation, the predicted strain level, shape, and internal energy of the workpiece are compared with the experimental specimens. A key point in the validation process is checking the internal energy. It is known that the ratio of stored energy to deformation energy ranges in the order of 30 %. The procedure for the experiments follows this methodology.
Keywords: high velocity forming; pressure distribution; uniform pressure coil; 620; 670